Analisis Kebutuhan Pengembangan Media Flashcard Pakaian Adat pada Mata Pelajaran IPS di Sekolah Dasar - Utami, Akdila Praka; Giyartini, Rosarina; Setiadi, Pidi Mohamad (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2023)
This study aimed to determine and analyze the needs of students for learning media in social studies class IV subjects in elementary schools. This research is based on the difficulties experienced by students in understanding the material and the non-optimal use of creative learning media. Data collection techniques were carried out through interviews, observations, and documentation by the subjects of this study were fourth-grade teachers and fourth-grade students at SDN 1 Kalangsari. The results obtained from this study show that the media used by the teachers is still not optimal and is less interesting. Image media printed on HVS paper tends to be easily damaged and not durable so after completing the lesson, the students feel bored to reuse the media. Thus, it can be concluded that there is a need for media development so that learning becomes more active and can attract the attention of students, one of which is using flashcards of traditional clothing in Indonesia with images sourced from Taman Mini Indonesia Indah (TMII). This media has the advantages of being easy to carry around, practical, durable, and can be used as an alternative game.